Investigational drugs for nasopharyngeal carcinoma. (3rd June 2017) - Ma, Brigette B.Y.; Hui, Edwin P; Chan, Anthony T.C.
ABSTRACT: Introduction : Nasopharyngeal carcinoma (NPC) is endemic to Southern China and Asia and is etiologically associated with the Epstein Barr virus (EBV). Whole exome and genome sequencing (WES, WGS) studies of NPC have reported several actionable therapeutic targets, and that the mutational load of NPC maybe comparable to that of squamous head and neck cancer. These unique biological characteristics have been exploited as potential targets and a wide range of investigational drugs are being investigated in clinical trials. Area covered : This review focused on the latest clinical development of the most promising classes of investigational agents in the treatment of advanced NPC. These include inhibitors of tumor angiogenesis, kinase signaling pathways and immunotherapy. Expert opinion : Checkpoint inhibitors and EBV-specific T-cell therapy have shown promising activity in early phase clinical trials, and are being further evaluated in randomized studies. For patients whose tumors express genetic alterations that are known to predict response to kinase inhibitors, novel trial designs such as an 'Umbrella' study may be considered given the abundance of targeted agents that are now available for clinical evaluation. It is envisioned that regulatory approval for new drugs for advanced NPC will occur in the near future.